Avaliação da remoção de nitrogênio e da comunidade microbiana em sistemas biológicos para o pós-tratamento de efluente de canil - Souza, Aline dos Reis (2019)
Nitrogen removal (N) is limited in anaerobic treatments, reason why it was required to install a post-treatment of dog effluent at the Parque Francisco de Assis Kennel Wasterwater Treatment Plant (PFA-WWTP). After the anaerobic septic-filter tank, were inserted in series, a submerged biological aerated filter (SBAF), secondary decanters (SD) and constructed wetlands . Thus, the objective of this work was to evaluate the influence of post-treatment and aeration time on SBAF on N removal. Different phases were monitored: F1 with 7 uninterrupted daily aeration hours, with oxygen application rate (OAR) of 0,00196 kg L-1 d-1; F2 with 5 uninterrupted daily aeration hours, with OAR of 0.00140 kg L-1 d-1; and F3 with intermittent daily aeration, every each 2 hours, with OAR of 0.00336 kg L-1 d-1. Weekly samples were collected from the reactors for analyzes such as chemical oxygen demand (COD), total nitrogen Kjeldahl (TNK), nitrite and nitrate; Polymerase chain reaction (PCR) detection and quantification of ammonia and nitrite oxidizing bacteria (AOB and NOB), denitrifying bacteria (DB) and pathogenic microorganisms; besides the detection and similarity assessment (PCR/DGGE- Denaturing gradient gel electrophoresis) bacterium domain. In order to infer the effect of oxygen saturation, an experiment was performed in bench bioreactors (SBAF), in triplicate, feeding them with PFA-WWTP effluent and sludge, submitted to constant daily aeration, with a OAR of 0.192 kg L-1 d-1, for three days. The collections occurred every two hours for 10 hours daily, with determination of dissolved oxygen (DO), nitrite, nitrate, quantification of AOB and NOB. The introduction post-treatment resulted in N removal in PFA-WWTP, achieving efficiencies in the three phases, respectively, of 21, 17 and 35% of TNK. F3 showed significant nitrification, with higher nitrate concentrations (3.0 mg L-1) in SBAF and higher COD removal efficiencies. Oxygen saturation in bench-scale bioreactors (OD: 9.7 mg L-1) did not result in nitrate concentration (2.7 mg L-1) significantly higher than F3 (p <0.05). However, it was verified a higher density of BOA (4.9x106 MPN 100 mL-1), BON (3.6x106 MPN 100 mL-1) and denitrifying (3.1x1023 MPN 100 mL-1) in SBAF in F3 comparing with the other evaluated phases. In the bench bioreactors, even higher AOB and NOB density (1.4x1012 and 9.2x1014 MPN 100 mL-1) were observed, as a function of higher OAR. AOB, NOB (genus Nitrobacter), DB and Giardia and Cryptosporidium pathogens were detected with specific primers for each group in all phases and treatment units. With primer of bacterial domain, the predominant genera in F1 were Clostridium and Bacillus, with 96% and 93% similarity, while in the other phases was the genus Thauera, with 99% similarity, related to denitrification. It was concluded that the post-treatment increased the capacity of effluent depuration and N removal by nitrification and denitrification. It is recommended that the operation of SBAF be similar to phase F3, a condition that allows combining efficiency and energy savings.